Young Women’s Sexual and Reproductive Health Post HPV Vaccination - Ports, Katie A. (2014)
In the present study the authors sought to explore, in greater depth, the impact that HPV vaccination has on college-aged women’s reproductive and sexual health. Qualitative interviews were conducted with 30 HPV-vaccinated, college women and analyzed for reoccurring themes. Although findings revealed that women’s HPV-related knowledge was suboptimal, most women correctly believed that they were still at risk for HPV after having received the vaccination. Women indicated that having the HPV vaccine made them more aware of sexually transmitted infections and prompted them to continue to take care of their sexual health. Women reported that having the HPV vaccine did not influence their condom use or birth control choices, and they believed that obtaining Pap smears was still important. These results help us to understand the impact of HPV vaccination on women’s reproductive and sexual health. These findings are promising and reinforce the importance of educating women about behaviors that will help them maintain reproductive and sexually healthy lives.